AB0532 Effect of prior therapy on the efficacy and safety of abatacept: 6-month analysis of the action study. (23rd January 2014) - Nüßlein, H.; Alten, R.; Galeazzi, M.; Lorenz, H.M.; Boumpas, D.; Nurmohamed, M.T.; Bensen, W.G.; Burmester, G.R.; Peter, H.H.; Rainer, F.; Pavelka, K.; Chartier, M.; et al.
Abstract : Background: Randomized controlled trials have demonstrated the long-term efficacy and favourable safety of abatacept (ABA) in RA patients (pts). 1 Previously we reported 6-month (mth) results of an interim analysis of German and Canadian pts enrolled in this study. 2 Objectives: Evaluate the effect of prior therapy on retention rate, efficacy and safety of ABA in RA pts treated in routine clinical practice in Europe and Canada. Methods: ACTION (AbataCepT In rOutiNe clinical practice) is a non-interventional, prospective, longitudinal study in ABA-treated RA pts. Here we present the 6-mth planned interim analysis in pts from all participating countries. Retention rates (Kaplan–Meier estimation) are reported for subgroups of pts failing ≥1 anti-TNF agents and by reason for previous failure. Safety was assessed in all pts and reported up to Aug 2011. Results: 1138/1114 pts were enrolled/evaluable; 86% of pts had reached mth 6 or discontinued ABA within 6 mths at time of analysis. Mean (SD) baseline characteristics were: age 56.5 (12.6) years (yrs); disease duration 11.0 (8.9) yrs; female 81.1%; RF+ 69.2%. Overall 6-mth retention rate (95% CI) was 88.6% (86.4, 90.4), 93.0% (85.9, 96.6) in pts who failed DMARDs and 88.1% (85.7, 90.0) in pts who failed biologic agents. Of 978 pts who failed prior biologics, 49.1% and 50.2% failed 1 or ≥2 anti-TNF agents, respectively, and 26.6%, 46.5% and 22.0% failed the previous biologic due to primary or secondary inefficacy or safety/tolerance, respectively. Retention rates (95% CI) were 89.2% (85.8, 91.8) and 86.7% (83.1, 89.5) in pts who failed 1 or ≥2 anti-TNF agents, respectively, and 84.4% (79.0, 88.6), 90.3% (86.9, 92.8), and 85.1% (79.1, 89.5) in pts who failed due to primary inefficacy, secondary inefficacy or safety/tolerance, respectively. 95 SAEs were reported in 54/1138 (4.7%) pts (20 discontinuations): 8 deaths including 4 due to serious infections, 19 serious infections, 8 malignancies, 5 cardiac disorders and 3 vascular disorders. No TB but one event of opportunistic infection was reported ( Pneumocystis jiroveci ). Conclusions: This long-term observational study of abatacept in RA pts in a real-life setting demonstrates similar retention rates at 6 mths independent of number or reason for failure of prior anti-TNF agents. Overall retention rate was consistent with data reported in interventional and real-life studies with abtacept. 3, 4 References: Genovese M et al. N Engl J Med 2005;353:1114–23. Nußlein H et al. Ann Rheum Dis 2011;70(Suppl 3):464. Poster FRI0359. Genovese M et al. Ann Rheum Dis 2008;57:547–54. Schiff M et al. Int J Clin Rheumatol 2010;5:581–91. Disclosure of Interest: H. Nüßlein Consultant for: Bristol-Myers Squibb, R. Alten Grant/Research support from: BMS, Merck Pharma GmbH, Wyeth Pharmaceuticals, Pfizer, Consultant for: Abbott Laboratories, Horizon Pharma, Merck Pharma GmbH, Nitec Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, Speakers Bureau: Abbott Laboratories, BMS, Horizon Pharma, Merck Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, M. Galeazzi: None Declared, H. Lorenz Grant/Research support from: Wyeth, Consultant for: Bristol-Myers Squibb, Wyeth/Pfizer, Essex, MSD, UCB, Chugai, Roche, Abbott, D. Boumpas: None Declared, M. Nurmohamed Grant/Research support from: BMS, MSD, Roche, Abbott, Pfizer and UCB, Consultant for: BMS, MSD, Roche, Abbott, Pfizer and UCB, Speakers Bureau: BMS, MSD, Roche, Abbott, Pfizer and UCB, W. Bensen Grant/Research support from: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi -Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, Consultant for: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi -Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, Speakers Bureau: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi -Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, G. Burmester Grant/Research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers Bureau: Bristol-Myers Squibb, H. Peter: None Declared, F. Rainer: None Declared, K. Pavelka Consultant for: Roche, Abbott, MSD, Speakers Bureau: Pfizer, MSD, M. Chartier: None Declared, C. Poncet: None Declared, C. Rauch Employee of: Bristol-Myers Squibb, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb